Beyond Access: Digital Literacy and Collaborative Capacity among Santriwati to Prevent Online Radicalization - Rahmah At Taymini; Yanti Dwi Astuti; Erika Febri Astuti; Aisyah Rizki Diyan Sadila (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
The internet and social media have become open spaces highly vulnerable to the spread of radical group propaganda, hoaxes, and hate speech. This condition has driven the emergence of digital literacy movements as a societal response to the various negative impacts of digital media. Digital literacy among religious groups is considered one of the effective approaches to countering misleading and divisive information. This study aims to measure the level of digital literacy among female students at the Diniyah Putri Islamic Higher Education Institution in Padang Panjang, using ten digital literacy competency indicators developed by Japelidi (Jaringan Pegiat Literasi Digital / Digital Literacy Activist Network). The research employs a mixed method sequential explanatory model, beginning with a quantitative approach to obtain a general overview, followed by qualitative methods to deepen the understanding of the quantitative data. The findings reveal that the students possess a moderate level of digital literacy, with a total index score of 76.9%. The highest component is the ability to access digital information, with an index score of 87.2%, indicating their technical proficiency in locating and retrieving information online. In contrast, the lowest score is found in the ability to collaborate digitally, at 66.3%, reflecting limited use of digital media for cooperative work and productive interaction. These findings highlight the need for a more holistic enhancement of digital literacy, particularly in the collaborative dimension, within religious educational environments